Gold finger formation studied by high-resolution mass spectrometry and in silico methods. Issue 9 (12th December 2014) - Laskay, Ü. A.; Garino, C.; Tsybin, Y. O.; Salassa, L.; Casini, A.
Abstract : Combining high-resolution MS and QM/MM studies to investigate the reactivity of gold compounds with zinc finger domains at a molecular level. Abstract : High-resolution mass spectrometry and quantum mechanics/molecular mechanics studies were employed for characterizing the formation of two gold finger (GF) domains from the reaction of zinc fingers (ZF) with gold complexes. The influence of both the gold oxidation state and the ZF coordination sphere in GF formation provided useful insights into the possible design of new gold complexes targeting specific ZF motifs.